PERENCANAAN PENAMBAHAN RELAY DIRECTIONAL EARTH FAULT (DEF) UNTUK GANGGUAN SATU FASA KE TANAH DI SALURAN 150 KV GARDU INDUK NUSA DUA – PESANGGARAN - Yuni Maheswari, G. A. P.; Dyana Arjana, I Gede; Indra Partha, Cok Gede (Jurnal SPEKTRUM; Vol 8 No 3 (2021): Jurnal SPEKTRUMDO - 10.24843/SPEKTRUM.2021.v08.i03.p6, 2021)
Disruption of short circuit flow of one ground phase that occurred on the transmission line 150 kV Nusa Dua-Pesanggaran Substation, causing blackouts to occur in the Nusa Dua Substation area extending to the surrounding area. The disruption that occurred failed to be secured because the GFR (Ground Fault Relay) relay could not detect the presence of a current interference so it failed to work. Assisted relays are needed to secure short circuit flow interference one phase to help the GFR relay, where the selected relay is the DEF (Directional Earth Fault) relay. Installation of auxiliary relays requires planning and relay setting steps to obtain Iset, TMS and trip time. Calculations that have been done get the results of the GFR relay working at a minimum interference of 1,200A while the DEF relay works at a minimum interference of 0.521A. The one-phase disruption detected on the 150 kV channel based on the simulation is below 300A. Def relay will work after the GFR relay does not manage to detect interference of one phase of the land with a time span of 0 - 0.3 seconds.